EMOTIONAL INTELLIGENCE - MAVROU , MARIA (Open Schools Journal for Open Science, 2024)
Emotional Intelligence (EI) encompasses the ability to identify, use, understand, and manage one’s emotions, as well as perceive and manage the emotions of others. This paper categorizes the skills of EI into intrapersonal skills, interpersonal skills, adaptability, and stress management. It discusses strategies to enhance EI, including identifying strengths and weaknesses, setting goals, and managing stress. Additionally, the paper explores the relationship between EI, confidence, and stress, and highlights the benefits of EI in building relationships, succeeding in various life domains, and promoting overall well-being. Finally, the paper advocates for the inclusion of EI education in school curricula to foster positive behavior and skill development among students.